ASME 2013 7th International Conference on Energy Sustainability 2013
DOI: 10.1115/es2013-18283
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Based Thermochemical Energy Storage for Concentrated Solar Power

Abstract: A sulfur based thermochemical energy storage cycle for baseload power generation is being developed under the support of US DOE Sunshot program. Solar heat is stored in elemental sulfur via thermal decomposition of sulfuric acid and disproportionation of sulfur dioxide into elemental sulfur and sulfuric acid. Heat energy is recovered upon sulfur combustion. On-sun decomposition of sulfuric acid in a solar furnace has been demonstrated between 650 and 850°C. Near equilibrium conversion was obtained at high temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The areas closer to the quartz are heated up to much higher temperatures than the middle or end of the honeycomb. With increasing operating temperatures the gap between the temperature of the front and back widens: at 650ºC, the front and back differ by little less than 100ºC; when operating at 850ºC the difference increases to over 200ºC [15]. Due to a short residence time of 0.5 seconds on average, the average temperature of the honeycomb is used for analysis.…”
Section: (Equation 2)mentioning
confidence: 99%
See 3 more Smart Citations
“…The areas closer to the quartz are heated up to much higher temperatures than the middle or end of the honeycomb. With increasing operating temperatures the gap between the temperature of the front and back widens: at 650ºC, the front and back differ by little less than 100ºC; when operating at 850ºC the difference increases to over 200ºC [15]. Due to a short residence time of 0.5 seconds on average, the average temperature of the honeycomb is used for analysis.…”
Section: (Equation 2)mentioning
confidence: 99%
“…Due to the products being liquids formed from gases, they will be favored by higher pressures in accordance to Le Chatelier's principle. Simulations show that the disproportionation rate increases predictably with pressure up to 30 bar, at which point it stops presenting significant changes [15]. Albeit, modelling tends to ignore many of the physical interactions which occur in the reactor vessel.…”
Section: (Equation 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…The nominal cost of sulfur, typically $0.06-0.16/kg [12,13], is far less than typical molten salts and low temperature oils which cost between $1.19/kg -$5.00/kg and $0.30/kg -$5.00/kg [14]. Wong et al [15] have previously demonstrated the use of an elemental sulfur based thermochemical storage cycle with energy stored via decomposition of sulfuric acid and recovered via combustion of elemental sulfur. Additionally, both Clark and Dowling [16] as well as Wentworth and Chen [17] have proposed TES using elemental sulfur and sulfur based compounds, respectively, in an isobaric configuration.…”
Section: Introductionmentioning
confidence: 99%